Gender differences in female and male Australian Football injuries — A prospective observational study of emergency department presentations. Issue 7 (July 2021) - Gill, Stephen D.; Stella, Julian; Lowry, Nicole; Kloot, Kate; Reade, Tom; Baker, Tim; Hayden, Georgina; Ryan, Matthew; Seward, Hugh; Page, Richard S.
Abstract: Objectives: To compare injury-profiles of females and males presenting to Emergency Departments (EDs) with an Australian Football injury. Design: Prospective observational study. Methods: All patients presenting to one of 10 EDs in Victoria, Australia, with an Australian Football injury were included in the study. Data were prospectively collected over a 10 month period, coinciding with a complete Australian Football season, including pre-season training and practice matches. Relevant information was extracted from patient medical records regarding injury-type, body part injured, investigations and treatments required. Female and male data were compared with chi-squared and Fisher's exact tests. Results: 1635 patients were included, of whom 242 (14.8%) were female. Females had a higher proportion of hand/finger injuries (34.3% v 23.4%), neck injuries (6.6% v 2.5%) and patella dislocations (2.9% v 0.6%). Males had a higher proportion of shoulder injuries (11.5% v 5.8%), skin lacerations (8.0% v 1.7%), and thorax/abdominal/pelvic injuries (5.7% v 2.1%). Concussion rates were similar between the genders, occurring in 14.1% of all patients. Anterior cruciate ligament injuries were infrequent (1.0%) and not significantly different between genders. Females received more imaging investigations (83.1% v 74.7%) and analgesia (62.4% v 48.5%). A higher proportion of males required admission to hospital (5.0% v 2.1%), usually for surgery. Conclusion: Australian Football injury profiles differed between females and males. Gender-specific injury prevention and management programs would be indicated based on the study findings.